Investigating the impact of hedge horizon upon hedging effectiveness: evidence from the national stock exchange of India / Mandeep Kaur and Kapil Gupta - Kaur, Mandeep; Gupta, Kapil (Accounting Research Institute (ARI), UiTM Shah Alam, 2019)
This study investigated the impact of hedge horizon upon hedging effectiveness in Indian equity futures market by comparing hedging performance of near, next and far month futures contracts of the NIFTY50 index and its 17 composite stocks. Hedging effectiveness was measured using two approaches, namely, Variance Reduction approach and RiskReturn approach. The study found that near month futures contracts are most effective when hedge effectiveness is measured using the variance reduction approach, whereas, far month futures contracts are found to be most effective using the risk-return approach. These results imply that for highly risk-averse investors (concerned with only minimization of risk), near month futures contracts enable effective hedging, whereas for less risk-averse investors (concerned with risk as well as return), far month futures contracts offer superior hedge effectiveness. The study also found that coefficient of correlation between spot and futures returns is a significant factor affecting variance reduction of returns and bears a direct relationship with it.